Malignant Melanoma in Anal Canal : A Case Report (TAJ: Journal of Teachers Association, 2009)
A 60 years old postmenopausal lady was admitted in the surgery department of Islami Bank Medical College Hospital with complaints of a lump in anal region and occasional per rectal bleeding for six months. Examination revealed a small well defined globular mass in anal canal which extended from the anal verge up to lower rectum internally. Internal part was ulcerated from where foul smelling discharge was coming out. She had no history of exposure to any radiation or any surgery over the anal canal. On radiogram of the chest a cannon ball shadow was found. Incisional biopsy of the lesion revealed malignant melanoma. Abdomino-perineal resection of rectum and anal canal was done for the lesion with an uneventful postoperative period. Adjuvant therapy could not be instituted because the patient could not afford it. The patient carried herself well until she died at the ninth month postoperatively. doi: 10.3329/taj.v21i2.3803 TAJ 2008; 21(2): 180-181